Motivation and Technological Innovation: Mapping the Digital Business Competitiveness in Lampung Province - Isnandar Agus; Irvan Patuan Marsahala Simamora; Teta Puti Sugesti; Hesti Ayuningtiyas (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study explores the link between technological innovation and the competitive advantage of household enterprises in Lampung Province (2024), specifically examining whether digital adoption facilitates business scaling. Methodology: Utilizing a qualitative descriptive framework, this study evaluates the spread of digital tools against competitiveness benchmarks, using firm characteristics and labor dynamics as control variables. Results: The analysis reveals a "digital development paradox." While urban centers such as Bandar Lampung show high connectivity (78.50%), 68.86% of enterprises remain stagnant at lower scales. Conversely, West Lampung demonstrates higher efficiency, where a 59.27% adoption rate correlates with a 66.03% prevalence of medium-scale businesses. This indicates that the impact of digitalization is contingent on existing business maturity. Conclusions: Digital access alone is insufficient for structural transformation in healthcare. In urban settings, technology often serves as a survival tool for the informal sector, rather than as a growth engine. With 93.01% of provincial enterprises operating at low-to-medium levels, a shift toward deep integration of production and supply chains is vital to escape economic traps. Limitations: This cross-sectional study lacked longitudinal depth, which limited the ability to observe changes over time. Contributions: This study successfully refutes the assumption that digital adoption automatically scales businesses. This emphasizes the need for strategic infrastructure equity and deeper technological integration.